Integrating Lean Manufacturing and Environmental Sustainability: A Framework for the Automotive Component Industry - Kemala, Arum Sahidina; Widaningrum, Dyah Lestari (Institute of Research and Community Outreach - Petra Christian University, 2025)
Environmental sustainability in the manufacturing industry has garnered widespread attention from researchers and practitioners. Many companies have adopted Lean Manufacturing (LM) principles to enhance their performance; however, they have often failed to reap the full benefits of implementing LM in terms of environmental sustainability. This study aims to build a framework combining LM and sustainability to improve environmental sustainability achievements and apply the framework in a company. The study employed a mixed-methods approach to gain an in-depth understanding of the integration of LM and sustainability in enhancing sustainable environmental performance. This study involved eight respondents in the Delphi, AHP, and FMEA processes (four managers and four supervisors). The findings indicate that the integration of LM and sustainability principles can improve environmental sustainability achievements, as demonstrated by the increase in the Environmental Sustainability Index (ESI = 92.8), which is measured based on three indicators of environmental sustainability: energy efficiency, material use, and water use. This study differs from previous works by operationalizing the PEMIC methodology as a practical framework for sustainable lean implementation in the automotive manufacturing sector. The findings of this study provide implications for the importance of environmental sustainability in achieving sustainable manufacturing performance.